2021
DOI: 10.7759/cureus.14254
|View full text |Cite
|
Sign up to set email alerts
|

Tectorial Membrane Injury, Frequently Identified in Adult Trauma Patients Who Undergo Occipital-Cervical Fusion for Craniocervical Instability

Abstract: Background In the absence of frank craniocervical dissociation, there is a lack of consensus regarding what patterns of craniocervical junction ligamentous injuries require occipital-cervical fusion. This study was undertaken to examine the integrity of the craniocervical junction ligaments and analyze clinical outcomes in patients who underwent occipital-cervical fusion for craniocervical junction injury. Methods Adult patients requiring occipital-cervical fusion were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Injuries to one or more of these major ligaments imply a greater risk for craniocervical instability and higher likelihood for occipital cervical fusion (Figure 4A-4D). Fiester et al identified nine patients who underwent emergent occipital cervical fusion for acute CDSI and found that all nine patients demonstrated a tear in the tectorial membrane and five patients sustained an alar ligament tear [20]. The importance of the major CCJ ligaments is supported from cadaveric studies that have investigated the in vitro biomechanical function of these three ligaments [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Injuries to one or more of these major ligaments imply a greater risk for craniocervical instability and higher likelihood for occipital cervical fusion (Figure 4A-4D). Fiester et al identified nine patients who underwent emergent occipital cervical fusion for acute CDSI and found that all nine patients demonstrated a tear in the tectorial membrane and five patients sustained an alar ligament tear [20]. The importance of the major CCJ ligaments is supported from cadaveric studies that have investigated the in vitro biomechanical function of these three ligaments [21].…”
Section: Resultsmentioning
confidence: 99%
“…However, the patient’s age and comorbidities play a major role in the overall morbidity and mortality of craniocervical and atlantoaxial trauma [ 11 ]. One recent study demonstrated wide variability in the types of osteoligamentous trauma and the number of torn CCJ ligaments in patients who underwent occipital cervical fusion for CDSI [ 20 ]. Furthermore, there has been wide variability in the surgical techniques and clinical management of patients with CDSI implying that further research and/or a more nuanced understanding of CDSI is warranted to improve patient care.…”
Section: Discussionmentioning
confidence: 99%
“…In recent literature, intact TM appears to be an important favorable prognostic factor in atlantooccipital dislocation which is considered to be a frequently fatal injury 12 . Fiester et al have proposed that the alteration of the supradental space (fat-lled space superior to the atlantoaxial joint, inferior to the basion of the clivus, and anterior to the TM) followed by injury of the TM may indicate a patient with signi cant CVJ instability [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Whereas, adverse events of posterior occipitocervical fusion were also reported including vascular injury, cerebrospinal fluid leakage, tectorial membrane injury even fixation failure. 9,10 As for the anterior approach treatments of occipitocervical fusion, the total en bloc spondylectomy using a combined approach 11 and reconstruction using a clival plate with titanium mesh cage have been reported. 12 Although these two methods can guarantee immediate immobility and achieve satisfactory bone fusion, lots of complications were reported including new neurologic deficit, implant failure, cerebrospinal fluid leakage and cervical nerve root injury.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Whereas, adverse events of posterior occipitocervical fusion were also reported including vascular injury, cerebrospinal fluid leakage, tectorial membrane injury even fixation failure. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%